Does Shoot Apical Meristem Function as the Germline in Safeguarding Against Excess of Mutations? - Burian, Agata (Frontiers in Plant Science, 2021)
A genetic continuity of living organisms relies on the germline which is a specialized cell lineage producing gametes. Essential in the germline functioning is the protection of genetic information that is subjected to spontaneous mutations. Due to indeterminate growth, late specification of the germline, and unique longevity, plants are expected to accumulate somatic mutations during their lifetime that leads to decrease in individual and population fitness. However, protective mechanisms, similar to those in animals, exist in plant shoot meristems allowing plants to reduce the accumulation and transmission of mutations. This review describes cellular mechanisms related to spatio-temporal distribution of cell divisions, organization of cell lineages, and cell fate specification to argue that meristematic cell lineages function analogous to animal germline.